Adiwiyata School Development at Kebun Bunga 5 State Elementary School - Anhar Yani; Semuel Risal; Wahyu Ekma (East Asian Journal of Multidisciplinary Research, 2023)
The research conducted by the author is qualitative research with an exploratory method of inductive approach. Data collection techniques are observation, interviews and documentation, interviews with three informants. The research location is SDN Kebun Bunga 5 Banjarmasin city. For data processing techniques the author uses data reduction, data presentation and drawing conclusions. Based on the results of the above research, the researcher provides suggestions, namely: First, launching a Knowledge Management program in terms of overcoming the adjustments and qualifications of teachers who are still unable to carry out thematic environmentalbased teaching. Second, start developing a business incubator as a source of additional funds to accelerate the addition of school infrastructure.